[PP.15.18] FINDING SUPPLEMENTS TO TRADITIONAL BP MONITORING: A CORRELATION RESEARCH ANALYSIS FROM MODEL NCD LIFESTYLE CLINIC, JODHPUR, INDIA. (September 2017) - Meena, J.; Raghav, P.; Rustagi, N.
Abstract : Objective: To monitor relationship between hypertension and indicators/risk factors in patients at model NCD lifestyle clinic (MNLC) and suggest supplementary indicators based on findings. Design and method: Present study was carried out at MNLC situated Urban Health Center (UHC) Pratap Nagar, Jodhpur. Secondary data i.e digital medical records of the patients (n = 1036) collected between Nov, 2015 to Nov, 2016 were analyzed using appropriate statistical tests (descriptive, pearson's correlation analysis). Data included patient's personal and clinical examination details, diagnosis, laboratory values, anthropometric measures etc. Confidentiality of the data was maintained and ethical approval obtained from Institutional ethical committee: AIIMS, Jodhpur. Results: The mean age of patients was 58 ± 4.6 years and majorly females (57.6%). Prevalent morbidities were: Hypertension (72.9%), Diabetes (23.7%) and Obesity (67.2%). The mean systolic (SBP) 152 ± 9.8 mmHg, diastolic blood pressure (DBP) 91 ± 5.7 mmHg, Fasting blood sugar 112 ± 7.4 gm/dl and total cholesterol (TC) 178 ± 12 gm/dl. Mean weight (BW) 76 + 5.4 kg, body mass index (BMI) was 26.4 ± 4.7, mean waist circumference (WC) 97.5 ± 7.2 cm and waist-hip ratio (WHR) 0.97 ± .17 reflecting the high burden of central obesity. Correlation analysis demonstrated positive relationship between BP-Weight (r = 0.88) BP-FBS (r = 0.76), BP-WHR (r = 0.70). However, the BP-BMI (r = 0.16) and BP-TC (r = 0.28) showed a weak positive relationship. Conclusions: Present research suggests BW, FBS and WHR demonstrate incremental risk trend towards rising BP, major pathology in hypertension. It is suggested that further research be conducted to devise research backed proxy indictors/risk factors as supplements to error prone tradition BP monitoring for improved clinical outcomes.